LISTENING JOURNALS FOR EXTENSIVE LISTENING PRACTICE OF EFL STUDENTS AT ANDALAS UNIVERSITY - Wulan Fauzanna (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Using audio from CD provided by textbook is a conventional method for learning listening, where teacher played the audio recording providing by the textbook in the language lab. This method is limited in providing the natural language features spoken by a variety of English speakers. Recently, teaching listening has been developed using internet media. There are many English language teaching sources available on the internet which provide audio, videos, and podcast. For learning purpose, the audio is also accomplished by several activities and transcript. In this method, learners practice extensive listening followed by completing listening journals, records of students’ listening practice and self-evaluation.   This study aimed to investigate the effectiveness of listening journal in helping students understand the overall meaning. The study has been conducted to the first year EFL university students during their dictation and reproduction lessons. Every week, students were required to do extra activities as homework. They are assigned to listen to several ELT sources on the internet. The results showed that most of the students found the method helped them to improve their vocabulary and understand the meaning from many different sources. Students relied on their listening ability and identify the weakness which needs improvement.This method appeared to be an effective listening teaching method since the students were exposed to English variety.